2019
DOI: 10.1016/j.fertnstert.2019.07.272
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-specific follicular steroidogenesis in ovarian stimulation: evidence from the menopur in GnRH antagonist single embryo transfer - high responder (MEGASET-HR) trial

Abstract: EBL). Spearman's correlation was used to evaluate the correlation between leiomyomata volume and operative outcomes. Receiver-operator-characteristic (ROC) curves were constructed for outcomes showing statistical significance.RESULTS: A total of 117 patients were included; there was no difference in the demographics or leiomyomata characteristics of patients undergoing MRI or US in the AM (n¼69), LM (n¼13) or RALM (n¼35) groups. The mean age and leiomyomata volume of patients undergoing LM was 36.7AE7.1 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, we must also consider the different effect of rLH and hCG on the steroidogenesis process, as an alternative explanation for the different endocrine profile. Previous studies comparing progesterone levels following OS with rFSH or HP-hMG have revealed similar findings; rFSH stimulation alone was associated with higher progesterone levels at the end of stimulation, even after adjusting for ovarian response [1,8,21,22]. In accordance to our study, a study by Sebag-Peyrelecade et al which compared the progesterone levels of rFSH+rLH treatment with those of hMG treatment, revealed that supplementation of rLH was not sufficient to decrease the progesterone levels to those observed in the hMG treatment cycles, unrelated to the degree of ovarian response [21].…”
Section: Discussionmentioning
confidence: 55%
“…However, we must also consider the different effect of rLH and hCG on the steroidogenesis process, as an alternative explanation for the different endocrine profile. Previous studies comparing progesterone levels following OS with rFSH or HP-hMG have revealed similar findings; rFSH stimulation alone was associated with higher progesterone levels at the end of stimulation, even after adjusting for ovarian response [1,8,21,22]. In accordance to our study, a study by Sebag-Peyrelecade et al which compared the progesterone levels of rFSH+rLH treatment with those of hMG treatment, revealed that supplementation of rLH was not sufficient to decrease the progesterone levels to those observed in the hMG treatment cycles, unrelated to the degree of ovarian response [21].…”
Section: Discussionmentioning
confidence: 55%
“…However, we must also consider the different effect of rLH and hCG on the steroidogenesis process as an alternative explanation for the different endocrine pro le. Previous studies comparing progesterone levels following OS with rFSH or HP-hMG have revealed similar ndings; rFSH stimulation alone was associated with higher progesterone levels at the end of stimulation, even after adjusting for ovarian response (1,8,21,22). In accordance to our study, a study by Sebag-Peyrelecade et al which compared the progesterone levels of rFSH + rLH treatment with those of hMG treatment, revealed that supplementation of rLH was not su cient to decrease the progesterone levels to those observed in the hMG treatment cycles, unrelated to the degree of ovarian response (21).…”
Section: Pn-pronucleimentioning
confidence: 54%